Assessment and Transplantation of Orphan Donor Livers: A Back‐to‐Base Approach to Normothermic Machine Perfusion. Issue 12 (15th September 2020) - Reiling, Janske; Butler, Nick; Simpson, Andrew; Hodgkinson, Peter; Campbell, Catherine; Lockwood, David; Bridle, Kim; Santrampurwala, Nishreen; Britton, Laurence; Crawford, Darrell; Dejong, Cornelius H. C.; Fawcett, Jonathan
Abstract : Globally, a large proportion of donor livers are discarded due to concerns over inadequate organ quality. Normothermic machine perfusion (NMP) allows for hepatocellular and biliary viability assessment prior to transplantation and might therefore enable the safe use of these orphan donor livers. We describe here the first Australasian experience of NMP‐preserved liver transplants using a 'back‐to‐base' approach, where NMP was commenced at the recipient hospital following initial static cold storage. In the preclinical phase, 10 human donor livers declined for transplantation (7 from donation after circulatory death [DCD] and 3 from donation after brain death [DBD]) were perfused using a custom‐made NMP setup. Subsequently, 10 orphan donor livers (5 from DCD and 5 from DBD) underwent NMP and viability assessment on the OrganOx  metra  device (OrganOx Limited, Oxford, United Kingdom). Both hepatocellular and biliary viability criteria were used. The median donor risk index was 1.53 (1.16‐1.71), and the median recipient Model for End‐Stage Liver Disease score was 17 (11‐21). In the preclinical phase, 'back‐to‐base' NMP was deemed suitable and feasible. In the clinical phase, each graft met predefined criteria for implantation during NMP and was subsequently transplanted. Five (50%) recipients developed early allograft dysfunction based on peak aspartate aminotransferase. To date, all grafts function satisfactorily, and none of the 5 recipients who received a DCD liver have developed cholangiopathy. The OrganOx  metra  using a back‐to‐base approach has enabled the safe use of 10 high‐risk orphan donor livers with 100% 6‐month patient and graft survival. NMP improved surgeon confidence to use orphan donor livers and has enabled a safe expansion of the donor pool.